Instrument Design Diagnostic Test Three-Tier Multiple Choice Redox Material with Redox Diagnostic Test Software (RDT) - Nurrohmah, Enur Siti; Susilaningsih, Endang; Nuswowati, Murbangun (Journal of Innovative Science Education, 2018)
This study aims to design a diagnostic test instrument misconceptions of Reduction and Oxidation reaction (redox) methods of Three-Tier Multiple Choice by developing Redox Diagnostic Test (RDT) software. The use of RDT can produce diagnostic test results of students' understanding immediately after the process of testing work. The understanding profiles experienced by the students in each class can be automatically captured so that the understanding of students' understanding time becomes shorter than the manual way. Although the testing work is done online, students cannot access the software outside the school computer lab so as to avoid the student dishonesty in the test. The research method used is Research and Development (R & D). The research model adopted in the Four-D development model with the research stage that is, define, design, develop, and dissemination. The result of content validation gets a score of 47 is on a very feasible criterion, so also media validation get score 28,5 is at very reasonable criteria. The results of the analysis of the level of understanding show that the test instrument using RDT software can diagnose understanding students well. Based on the small and large scale test set 19 item questions used in the test instrument. The result of instruments reliability test on the large-scale test by using KR-21 formula is 0,72 which belongs to a good category.